PENGARUH DISKON SHOPEE TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA - Saeful Anwar; Najla Kayla; Azzam Izzudin; Nabil Makarim; Mia Lasmi Wardiyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The discounts offered by the e-commerce platform Shopee on students' purchasing decisions are the subject of this research. Discounts are one of the promotional tactics commonly used to attract customers, especially students who are price-sensitive. For this research, a quantitative survey method was used. 30 respondents were students who had previously shopped on Shopee. The instrument validity and reliability tests and prerequisite analyses included normality tests. Data were processed using SPSS Statistics 27. The influence of discounts on purchasing decisions was measured through simple linear regression data analysis. The results showed that discounts significantly affect students' purchasing decisions. These findings highlight the importance of promotions with discounts to draw young customers to make purchases.